2009
DOI: 10.1002/ajh.21564
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treatment‐related liver toxicity on the outcome of HCV‐positive non‐Hodgkin's lymphomas

Abstract: We studied 160 Hepatitis C virus (HCV)-positive patients with NHL (59 indolent NHL, 101 aggressive). Median age was 67 years. HCV-RNA was present in 146. HBsAg was positive in seven patients. At diagnosis, ALT value was above UNL in 67 patients. One hundred and twenty patients received an anthracycline-based therapy, alkylators, 28 received chemotherapy plus rituximab. Cytotoxic drugs dose was reduced in 63 patients. Among 93 patients with normal ALT at presentation, 16 patients developed WHO grade II-III live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 26 publications
2
47
0
Order By: Relevance
“…8,10,12,15,17 In our study, the only risk factor for severe hepatotoxicity was an increase in base-line value of ALT, similar to findings in the Japanese study. 3 So far, only a few studies have evaluated the prognosis of HCV-positive DLBCL.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 90%
See 2 more Smart Citations
“…8,10,12,15,17 In our study, the only risk factor for severe hepatotoxicity was an increase in base-line value of ALT, similar to findings in the Japanese study. 3 So far, only a few studies have evaluated the prognosis of HCV-positive DLBCL.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 90%
“…8 In fact, we did not record any difference in terms of severe hepatotoxicity between the patients treated with R-CHOP and those treated with CHOP, while, after adjusting by prognostic factors, patients treated with R-CHOP displayed a better OS and PFS. Interestingly, in the subgroup of patients monitored with viremia, the viral load invariably increased after treatment with R-CHOP (or CHOP), in agreement with the findings of Ennishi et al 3 However, we did not find any clear direct relation between the increase in HCV-RNA and severe hepatotoxicity.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…There is a two-to four-fold increased risk of developing B-NHL among HCV-positive patients [1][2][3][4]. In comparison to their negative counterparts, HCV-associated B-NHL (i) are more often marginal zone lymphomas (MZL) and diffuse large B-cell lymphomas (DLBCL) [4], (ii) often display extranodal localization [3], (iii) and have higher rates of liver toxicity after treatment by chemotherapy [5][6][7][8]. HCV-associated lymphomas have also been shown to be frequently associated with type II mixed cryoglobulinemia (MC) [9,10], which are immunoglobulin complexes containing both a polyclonal IgG and a monoclonal IgM rheumatoid factor (RF) directed against the IgG.…”
Section: Introductionmentioning
confidence: 99%
“…There are conflicting evidence about the patients with HCV positivity and undergoing chemotherapy. Besides the studies that reported only mild-moderate elevations in liver enzymes of HCV positive patients with hematological malignancy undergoing chemotherapy (Zuckerman et al, 1998), in a recent review of 160 non-Hodgkin lymphoma patients with chronic hepatitis C, it was reported that 15% of them had significant liver toxicity (Arcaini et al, 2010). Also in diffuse large B-cell lymphoma patients, it was shown that, overall survival was significantly worse in the patients with chronic HCV infection than those without HCV infection (at a median follow up of two years overall survival rates were 56% and 80% respectively and p 0.02) (Besson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%